Clinical Characteristics and Outcomes of Staphylococcus lugdunensis Prosthetic Joint Infections: A Multicenter Retrospective Analysis - Masood, Komal; Redfern, Roberta E.; Duggan, Joan M.; Georgiadis, Gregory M.; Suleyman, Geehan (Orthopedics (Thorofare, N.J.), 2020)
Staphylococcus lugdunensis has been increasingly recognized as a cause of serious infections, particularly prosthetic joint infections (PJIs). The aim of this study was to describe the clinical characteristics, treatments, and outcomes of S lugdunensis PJIs. This was a retrospective multicenter study of consecutive adult patients with S lugdunensis PJIs from January 2007 through December 2017; 28 patients met inclusion criteria. The knee was the most commonly affected joint (67.9%), followed by the hip (25%). Clinical and microbiologic characteristics, treatment modalities, and outcomes were evaluated. Thirteen (46.4%) patients had two-stage revision, 9 (32.1%) had debridement with or without revision, 5 (21.4%) had no surgical intervention, and 1 (3.6%) had one-stage revision. Twenty-four (85.7%) patients had monomicrobial infection with S lugdunensis , whereas 4 had polymicrobial. Two patients had concomitant bacteremia. All isolates, except 1, were susceptible to oxacillin. Three patients with no surgical intervention received oral antibiotics, 2 were not treated, and 1 was discharged to hospice. Relapse was observed in 2 of 13 (15%) patients who had two-stage revision, 4 of 9 (44%) who had debridement, and 6 of 6 (100%) who had no surgical intervention or one-stage revision regardless of antibiotic treatment regimen. There was a significant difference in cure rate for patients who underwent two-stage revision compared with other treatment modalities (85% vs 33%, P =.009). Appropriate management of S lugdunensis PJI includes both aggressive surgical treatment and a prolonged course of antibiotics and is associated with excellent clinical response. Regardless of route or duration of antibiotic therapy, relapse is high for patients not treated with two-stage revision. [ Orthopedics . 2020;43(6):345–350.]